Effects of host diversity and other management components on epidemics of potato late blight in the humid highland tropics - Nelson, R. J.; Mundt, C. C.; Chacón, G.; Jaramillo, R. E.; Forbes, G.A.; Garrett, Karen A. (My University, 2007)
A field study at three highland sites near Quito, Ecuador, was conducted to determine whether host-diversity effects on potato late blight would be as important as recently found in studies conducted in temperate areas. We compared three potato mixtures and use of mixtures in combination with different planting densities and two fungicide regimes. Treatment comparisons were made by absolute and relative measures of host-diversity effects and incorporating a truncated area under the disease progress curve as a means of standardizing comparisons across sites. Potato-faba intercrops consisting of only 10% potato provided an estimate of the effects of dilution of susceptible host tissue. Host-diversity effects were very different across study sites, with a large host-diversity effect for reduced disease only at the site most distant from commercial potato production. Planting density had little influence on host-diversity effects or on late blight in single-genotype stands. Fungicide use in combination with potato mixtures enhanced a host-diversity effect for reduced late blight. Potato-faba intercrops produced only a small decrease in potato late blight. Effects of host diversity on yield were variable, with the greatest increase in yield for mixtures treated with fungicides at the site most distant from commercial potato production. The effects of host diversity on late blight severity may be less consistent in the tropical highlands than in the temperate zone, but can contribute to integrated disease management.
Citation: Garrett, K., . . . & Forbes, G. (2001). The Effects of Host Diversity and Other Management Components on Epidemics of Potato Late Blight in the Humid Highland Tropics. Phytopathology, 91(10), 993-1000. https://doi.org/10.1094/PHYTO.2001.91.10.993
Keywords: Host diversity; Potato late blight; Cultivar mixtures; Genotype diversity; Intercropping; Phytophthora infestans